Exploring local immunological adaptation of two stickleback ecotypes by experimental infection and transcriptome‐wide digital gene expression analysis. Issue 3 (13th September 2012) - Lenz, Tobias L.; Eizaguirre, Christophe; Rotter, Björn; Kalbe, Martin; Milinski, Manfred
Abstract Understanding the extent of local adaptation in natural populations and the mechanisms that allow individuals to adapt to their native environment is a major avenue in molecular ecology research. Evidence for the frequent occurrence of diverging ecotypes in species that inhabit multiple ecological habitats is accumulating, but experimental approaches to understanding the biological pathways as well as the underlying genetic mechanisms are still rare. Parasites are invoked as one of the major selective forces driving evolution and are themselves dependent on the ecological conditions in a given habitat. Immunological adaptation to local parasite communities is therefore expected to be a key component of local adaptation in natural populations. Here, we use next‐generation sequencing technology to compare the transcriptome‐wide response of experimentally infected three‐spined sticklebacks from a lake and a river population, which are known to evolve under selection by distinct parasite communities. By comparing overall gene expression levels as well as the activation of functional pathways in response to parasite exposure, we identified potential differences between the two stickleback populations at several levels. Our results suggest locally adapted patterns of gene regulation in response to parasite exposure, which may reflect different local optima in the trade‐off between the benefits and the disadvantages of mounting an immune response because of quantitative differences of the local parasite communities.